Estimating cost structures in the U.S. nuclear power industry - Supawat Rungsuriyawiboon (2018)
With growing concerns about global warming and surging oil prices, nuclear power is now back on the U.S. energy policy agenda. This paper provides firm level analysis of the production technology and cost structures in the U.S. nuclear power generation industry. The paper applies an econometric approach into a dual restricted variable cost function within a "temporal equilibrium" framework. A panel data set of 32 nuclear power generations for major U.S. investor owned utilities over the period 1986-2002 is used. The major finding indicates that most electric utilities in the nuclear electricity generation industry over utilized capital in production. The estimated results show evidence of scale economies in the production of the electricity industry. The paper presents supporting evidence that nuclear technology is cheaper than other alternative technologies and fuels, and it can offer possible cost savings to other alternative technologies.